2019
DOI: 10.15453/2168-6408.1513
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experiences of Occupational Therapists in Transitioning to Leadership Roles

Abstract: Background: Several studies on leadership in occupational therapy have discussed the key qualities of leadership and its importance, even though little is known about the transition process into leadership roles. This research examined the lived experiences of occupational therapists who have transitioned from a clinical to a leadership role and identified the supports and challenges that were found to be important. Methods: Semi-structured interviews were used to gain insight into the transition process of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Our ndings found that a strategic clinical leader in an HIV system is a team leader who provides direction and guidance, suggesting the need for collaboration with other leaders and team members in providing HIV care. Consistent with this nding, successful strategic leaders depend on teams because it brings collective expertise and enhances patient care (33)(34)(35)(36). In addition, clinical leaders direct and help people (15,37).…”
Section: Discussionmentioning
confidence: 85%
“…Our ndings found that a strategic clinical leader in an HIV system is a team leader who provides direction and guidance, suggesting the need for collaboration with other leaders and team members in providing HIV care. Consistent with this nding, successful strategic leaders depend on teams because it brings collective expertise and enhances patient care (33)(34)(35)(36). In addition, clinical leaders direct and help people (15,37).…”
Section: Discussionmentioning
confidence: 85%
“…The physical therapists in this study did exactly that, recognizing consistencies between their clinical identities and their developing identities as leaders. This finding conflicts with the majority of literature on clinicians turned managers/leaders from other health-care professions and exposes a paradox in the existing PT leadership literature (Masoumi, 2019;Shams et al, 2019;Spehar et al, 2012). The existing body of research in PT leadership often frames leadership/management skills as separate from other skills in the physical therapist's repertoire (Green-Wilson, 2011;Lopopolo et al, 2004;McGowan et al, 2016;Schafer et al, 2007;Silberman et al, 2020;Tschoepe et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…The participants all demonstrated an ability to use discomfort as a stimulus to develop a leader identity. Feeling overwhelmed, facing a steep learning curve and feeling discomfort in the departure from patient care are common experiences among new health-care leaders (Shams et al , 2019; Sonnino, 2016; Thompson and Henwood, 2016; Glendinning, 1987; Green-Wilson and Zeigler, 2020; Lopopolo et al , 2004; McGowan et al , 2016; Silberman et al , 2020). The manner in which the physical therapists in this study responded to discomfort is what makes this finding unique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perceived lack of trust from previous frontline colleagues, as expressed by this study's participants, was also experienced in nursing where it was found that although much emphasis was placed on the relationship of trust between patients and nurses, this did not translate to that of trust between the nurse and their manager (19). A study exploring the lack of trust between clinicians and managers, found that managers were often 'between a rock and a hard place' due to carrying out instructions from senior managers and the time pressures of their roles restricted them from the very important face-to-face discussions with their clinicians that allows trustworthiness to be developed (20).…”
Section: Discussionmentioning
confidence: 99%